Implementation and Utilization of Family Latrines in Allu Hamlet, Minasa Baji Village, Bantimurung Sub-district, Maros Regency - Suminar, Saka; Bare Telan, Albina; M Dukabain, Olga; Suluh, Debora G; Vanchapo, Antonius Rino; Agustina, Agustina; Aulia Rahmat, Rezqiqah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Based on data obtained from local agencies, it was recorded that there were 155 family heads in Allu Hamlet, Minasa Baji Village, Bantimurung District, Maros Regency, but only 60% of family heads had family latrines that met the requirements or health standards, thus there were still 40% of family heads who did not have family latrines that met the requirements, this could be a big problem if not immediately addressed, because it could be the cause of environmental pollution which in turn could cause various diseases. The purpose of the study was to determine the utilization of family latrines in Allu Hamlet, Minasabaji Village, Bantimurung District, Maros Regency. This type of research is